Informal Economy and Poverty in Urban Nepal - Adhikari, Dipak Bahadur (Economic Journal of Nepal, 2018)
Informal sector plays a crucial role in employing a significant part of the economically active population of Nepal. The Nepal Labour Force Survey(NLFS) - 2017/18 has estimated around 62 percent of people to be currently employed in the informal sector. It is estimated that there are 84.6 percent of the currently employed who are informally employed in all industries as compare to formal employment 15.4 percent in Nepal. Employment is the main source of income of poor people which is still considered to be the most effective vehicle to take them out of poverty. People of rural areas are gradually coming to urban areas. So, economic growth and structural changes are increasingly linked to urbanization process. More people will live in urban settlements than in rural areas. Metropolitan cities of Nepal like Lalitpur can offer the lure of better employment, education, and healthcare and they also contribute disproportionately to the economy of the country. However, rapid urban expansion is often associated with poverty and rapid growth of informal sector urban area.